Pseudomonas syringae DC3000 infection increases glucosylated N-glycans in Arabidopsis thaliana - Gernot Beihammer; Andrea Romero-Pérez; Daniel Maresch; Rudolf Figl; Réka Mócsai; Clemens Grünwald-Gruber; Friedrich Altmann; Els J. M. Van Damme; Richard Strasser (Glycoconjugate Journal, 2023)
Studying the interaction between the hemibiotrophic bacterium Pseudomonas syringae pv. tomato DC3000 and Arabidopsis thaliana has shed light onto the various forms of mechanisms plants use to defend themselves against pathogen attack. While a lot of emphasis has been put on investigating changes in protein expression in infected plants, only little information is available on the effect infection plays on the plants N-glycan composition. To close this gap in knowledge, total N-glycans were enriched from P. syringae DC3000-infected and mock treated Arabidopsis seedlings and analyzed via MALDI-TOF–MS. Additionally, fluorescently labelled N-glycans were quantified via HPLC-FLD. N-glycans from infected plants were overall less processed and displayed increased amounts of oligomannosidic N-glycans. As multiple peaks for certain oligomannosidic glycoforms were detected upon separation via liquid chromatography, a porous graphitic carbon (PGC)-analysis was conducted to separate individual N-glycan isomers. Indeed, multiple different N-glycan isomers with masses of two N-acetylhexosamine residues plus 8, 9 or 10 hexoses were detected in the infected plants which were absent in the mock controls. Treatment with jack bean α-mannosidase resulted in incomplete removal of hexoses from these N-glycans, indicating the presence of glucose residues. This hints at the accumulation of misfolded glycoproteins in the infected plants, likely because of endoplasmic reticulum (ER) stress. In addition, poly-hexose structures susceptible to α-amylase treatment were found in the DC3000-infected plants, indicating alterations in starch metabolism due to the infection process.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Cutting off the power: inhibition of leukemia cell growth by pausing basal ATP release and P2X receptor signaling? - Carola Ledderose; Tobias Woehrle; Stephan Ledderose; Katharina Strasser; Richard Seist; Yi Bao; Jingping Zhang; Wolfgang G. Junger (Purinergic Signalling, 2016)

Unraveling the function of Arabidopsis thaliana OS9 in the endoplasmic reticulum-associated degradation of glycoproteins - Silvia Hüttner; Christiane Veit; Jennifer Schoberer; Josephine Grass; Richard Strasser (Plant Molecular Biology, 2012)

A comparison of recent and fossil large, high-spired gastropods and their environments: the Nopparat Thara tidal flat in Krabi, South Thailand, versus the Swiss Kimmeridgian carbonate platform - Richard Waite; André Strasser (Facies, 2011)

Sialic acid concentrations in plants are in the range of inadvertent contamination - Reinhard Zeleny; Daniel Kolarich; Richard Strasser; Friedrich Altmann (Planta, 2006)

Unaltered complex N-glycan profiles in Nicotiana benthamiana despite drastic reduction of β1,2-N-acetylglucosaminyltransferase I activity - Richard Strasser; Friedrich Altmann; Josef Glössl; Herta Steinkellner (Glycoconjugate Journal, 2004)

Two closely related forms of UDP-GlcNAc: α6-D-mannoside β1,2-N-acetylglucosaminyltransferase II occur in the clawed frog Xenopus laevis - Jan Mucha; Barbara Svoboda; Sonja Kappel; Richard Strasser; Peter Bencur; Ulrike Fröhwein; Harry Schachter; Lukas Mach; Josef Glössl (Glycoconjugate Journal, 2002)